Thermal Conductivity Enhancement of Al2O3 Nanofluid in Ethylene Glycol and Water Mixture - N. A., Usri; Azmi, W. H.; R., Mamat; Khamisah, Abdul Hamid (Elsevier Ltd, 2015)
The ability of nanofluids that exhibits enhanced thermal performance is acknowledged by researchers through studies since decades ago. However, the observation of thermal properties for nanofluids in water and ethylene glycol based is not fully explored yet. Hence, this paper presents the thermal conductivity of water and ethylene glycol (EG) based Al2O3 nanofluid. The 13 nm sized Al2O3 nanoparticles were dispersed into three different volume ratio of water:EG such as 40:60, 50:50 and 60:40 using two-step method. The measurement of thermal conductivity was performed using KD2 Pro Thermal Properties Analyzer at working temperature of 30 to 70 oC for volume concentration of 0.5 to 2.0 %. The results indicate that the thermal conductivity increases with the increase of nanofluid concentration and temperature. While, as percentage of ethylene glycol increase, the range of thermal conductivity decrease due to ethylene glycol properties. The measurement data of the nanofluids give maximum enhancement of thermal conductivity at condition 2.0 % volume concentration, temperature of 70 oC and for all base fluid.